Advances and potentials of NiOx surface treatments for p−i−n perovskite solar cells - Tiwari, Nidhi (2023)
The performances of perovskite solar cells (PSCs) largely depend on the perovskite compositions and the selection of electron and hole transport layers (ETL and HTL). The p-type NiOx films have been largely used as HTL in p-i-n PSCs thanks to their high transparency, processing versatility, cost-effectiveness, and easy integration within tandem devices. Several studies have shown that surface modifications on NiOx films remove the surface defects, increase the NiOx conductivity, alter the band offset consequently improving the interfaces between NiOx film and the perovskite active layer. Indeed, besides improving the NiOx intrinsic properties, the surface treatments also lead, in many cases, to superior perovskite quality driving high photovoltaic performance. In this review, approaches of surface modifications based on physical (UV-ozone, oxygen, argon, and/or helium plasma), chemical (interlayer passivation), and doping treatments and their impacts on the structural and optoelectronic properties of the NiOx are examined and discussed. Furthermore, the effects of modified NiOx films in p-i-n PSCs power conversion efficiency (PCE) are also assessed together with the current challenges and future outlooks.